2018
DOI: 10.1111/ggi.13259
|View full text |Cite
|
Sign up to set email alerts
|

Oral function as an indexing parameter for mild cognitive impairment in older adults

Abstract: Oral motor skill, such as lip movement, might be impaired in patients with MCI. Detecting decreasing oral motor dexterity supports the early detection of MCI, and might be key to improve the prognosis of dementia. Geriatr Gerontol Int 2018; 18: 790-798.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
5
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 30 publications
(63 reference statements)
1
28
5
1
Order By: Relevance
“…We believe that compared with spontaneous speech tasks used in other studies [ 6 , 36 ], both these tasks tapped the speaker’s ability to rapidly change between different places of articulation, thus having a high speech planning load. This result aligns with many previous studies on temporal changes in the speech of individuals with cognitive impairment [ 11 , 12 , 25 ]. It is possible that the lower speech tempo and more hesitation time in utterances is a consequence of low language processing speed and disordered speech planning abilities.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We believe that compared with spontaneous speech tasks used in other studies [ 6 , 36 ], both these tasks tapped the speaker’s ability to rapidly change between different places of articulation, thus having a high speech planning load. This result aligns with many previous studies on temporal changes in the speech of individuals with cognitive impairment [ 11 , 12 , 25 ]. It is possible that the lower speech tempo and more hesitation time in utterances is a consequence of low language processing speed and disordered speech planning abilities.…”
Section: Discussionsupporting
confidence: 92%
“…Diadochokinesis is a task that has been widely used for checking speech planning abilities. Previous studies have suggested its potential to detect individuals with MCI from HCs [ 11 , 12 ]. In this task, we extracted the same features used in the tongue twister task.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk of death is also significantly increased in those with oral frailty (Iwasaki et al., 2018). It has been reported that oral motor skills, such as lip movement, are impaired in patients with cognitive impairment (Watanabe et al., 2018). These lines of evidence suggest that a reduced oral function is an important factor for physical frailty and is associated with cognitive impairment (See Figure 2).…”
Section: Tooth Loss and Frailty/sarcopeniamentioning
confidence: 99%
“…The characteristics of the participants of the present study, which included MMSE scores, the prevalence of cognitive impairment, educational history, maximum walking speed and Tokyo Metropolitan Institute of Gerontology Index of Competence, were similar to other large-scale cohort studies carried out in Japan. [18][19][20] Therefore, the samples in this study were regarded as representative of community-dwelling older individuals in Japan.…”
Section: Discussionmentioning
confidence: 99%